Timely evaluation in international development - and Webster, Jayne; Exley, Josephine; Copestake, James; Davies, Rick; Hargreaves, James (Journal of Development Effectiveness, 2018)
Impact and process evaluations are increasingly used in international development; however they are generally retrospective in outlook. A more timely approach to evaluation aims to identify necessary, feasible and effective changes during a programme or intervention’s lifetime. This paper aims to identify, categorise, describe and critically appraise methods to support more timely evaluation in international development. Potential methods were identified through scoping seminar, public symposium, targeted review of the literature, and the authors’ own experiences and opinions. Findings from the different data sources were reviewed collectively by the author group and triangulated to develop an analytical framework. We identified four purposes of timely evaluation for international development, and critiqued the use of approaches against four dimensions of timeliness and flexibility. Whilst we found significant interest in more timely approaches to evaluation in international development, there was a dearth of published empirical evidence upon which to base strong recommendations. There is significant potential for timely evaluation to improve international development outcomes. New approaches to mixing and adapting existing methods, together with new technologies offer increased potential. Research is needed to provide an empirical evidence base upon which to further develop the application, across sectors and contexts, of timely evaluation in international development.
Keywords: Adaptive learning; Outcome evaluation; Programme improvement; impact evaluation